2002
DOI: 10.2134/jeq2002.2680
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry and Photoinduced Toxicity of Acifluorfen, a Diphenyl‐Ether Herbicide

Abstract: Photochemistry studies can be helpful in assessing the environmental fate of chemicals. Photochemical reactions lead to the formation of by-products that can exhibit different toxicological properties from the original compound. For this reason the photochemical behavior of the herbicide acifluorfen (5-[2-chloro-4-(trifluoromethyl)phenoxy]-2-nitrobenzoic acid) in the presence of different solvents was studied. Photochemical reactions were carried out using a high-pressure mercury arc and a solar simulator. Kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…4) Decarboxylation via α-cleavage is the main photoreaction of acifluorfen. The homolytic mechanism via S 1 was proposed in acetonitrile, 87) while the heterolytic mechanism via short-lived T 1 was considered in water. 88) Acaricide cyflumetofen was rapidly photodegraded to the decarboxylated derivative with carboxylation at the 2-position of the 4-tert-butylphenyl ring, 4) which may be accounted for by the successive homolytic α-cleavage and rearrangement.…”
Section: Photo-induced Bond Cleavage 311 Carboxylic Acid Derivativmentioning
confidence: 99%
See 1 more Smart Citation
“…4) Decarboxylation via α-cleavage is the main photoreaction of acifluorfen. The homolytic mechanism via S 1 was proposed in acetonitrile, 87) while the heterolytic mechanism via short-lived T 1 was considered in water. 88) Acaricide cyflumetofen was rapidly photodegraded to the decarboxylated derivative with carboxylation at the 2-position of the 4-tert-butylphenyl ring, 4) which may be accounted for by the successive homolytic α-cleavage and rearrangement.…”
Section: Photo-induced Bond Cleavage 311 Carboxylic Acid Derivativmentioning
confidence: 99%
“…118) Although several energy quenching and radical scavenging experiments of acifluorfen suggested homolytic C-O cleavage from S 1 in acetonitrile, 87) photo-induced base-catalyzed ether cleavage was proposed instead in water. 88) Therefore, the reaction mechanism seems to be dependent on the solvent and the pH.…”
Section: Ethersmentioning
confidence: 99%
“…This means that the rate of photolysis of Schiff base increase with increasing the polarity of solvent and consistent with previous photolysis studies (S. K. Pramanikabc and S.Dasb, A. Bhattacharyyaa , 2008) . A possible explanation for the higher photolysis rate in polar solvents is due to the contribution of an oxygen independent mechanism which enhanced photolysis reaction (R. Kumar and M. Yusuf, 2009) and polar solvents would achieve better stabilization of the free ions (L. Scrano, 2002 ).…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…Photolysis conversion of the bischromones is found to be dependent upon the nature of the intermediate spacer and H-donating capability of the solvent. L. Scrano et al (L. Scrano et al, 2002) reported the direct photolysis of acifluorfen in different solvents (water, methanol, acetonitrile and n-hexan) by UV mercury lamp. On the other hand,J.…”
Section: Introductionmentioning
confidence: 99%
“…7-9 This motif also appears in biologically active natural products, notably in the mammalian hormone thyroxine 10 and the vancomycin family of antibiotics. 11 There has been recent interest in the synthesis of atropisomeric diaryl ethers 12,13 as these may have application as molecular gears.…”
mentioning
confidence: 99%